Design and fabrication of smart box conceal for letter and parcel / Muhammad Harraz Hazim Noor Azhar and Zeno Michael - Noor Azhar, Muhammad Harraz Hazim; Michael, Zeno (School of Mechanical Engineering, 2023)
The proposed project aims to address the vulnerabilities of traditional mailboxes by introducing an innovative smart box that enhances protection and security for letters and parcels. This durable and weather-resistant box, constructed with high-quality materials like steel and aluminium, ensures longevity and reliability. It incorporates cutting-edge technology such as GPS tracking and real-time alerts to provide users with up-to-date information on delivery location and status. Advanced security features, including biometric access controls and reinforced locks, prevent unauthorized access and theft. Manufactured with precision and quality through bending, cutting, and welding processes, the smart box accommodates letters and parcels in a safe and secure manner. With dimensions of up to 40cm x 35cm x 65cm, this smart box offers an effective solution to the challenges of modern mail delivery, combining innovative design, advanced technology, and high-quality materials